Longitudinal quantification of radical bursts during pulmonary ischaemia and reperfusion†. (5th January 2015) - Gielis, Jan F.; Boulet, Gaëlle A.; Briedé, Jacob J.; Horemans, Tessa; Debergh, Tom; Kussé, Max; Cos, Paul; Van Schil, Paul E.Y.
Abstract : OBJECTIVES: Pulmonary ischaemia–reperfusion injury (IRI) is associated with several life-threatening pulmonary disorders, and may severely compromise the outcome of lung transplantation. Highly reactive molecules such as superoxide, nitric oxide (NO) and peroxynitrite (ONOO − ) are presumed to contribute to IRI pathogenesis, but this assumption is based on indirect measurements. We use electron spin resonance (ESR) to directly quantify free radical formation after pulmonary ischaemia and reperfusion. METHODS: Five groups of 10 Swiss mice were subjected to left pulmonary hilum clamping for 1 h of ischaemia followed by 0, 1, 4 and 24 h of reperfusion or to sham thoracotomy alone as control procedure. In five mice per group, ESR was used to measure iron-diethyldithio-carbamate trihydrate-trapped NO in the lung. In the other group of 5, reactive oxygen species generation in the lung and in blood was quantified with ESR by detection of ascorbyl radical and CMH spin probe, respectively. Pulmonary ONOO − was monitored with nitrotyrosine Western blotting. RESULTS: After 1 h of reperfusion, a pulmonary NO peak (14.69 ± 0.91 × 10 4 Arbitrary Units (A.U.). vs 1.84 ± 0.75 × 10 4 A.U. in sham; P < 0.001) coincided with a significant increase in nitrosated proteins (0.105 ± 0.015 A.U.) compared with sham (0.047 ± 0.006 A.U.); P < 0.005). Peripheral blood showed a significant free radical burst after 1 h of ischaemia (11 774 ± 728 A.U. vs 6660 ± 833 A.U. in sham; P < 0.001). CONCLUSIONS: Longitudinal quantification of free radicals during IRI reveals the occurrence of two major radical bursts. The radical peak in peripheral blood after ischaemia may be related to systemic hypoxia. After 1 h of reperfusion, the lung tissue shows a significant increase of superoxide, NO and their reaction products, which are probably involved in IRI pathogenesis.